Effect of Dexamethasone on Postoperative Sore Throat in the Patients Undergoing Elective Orthopaedic Surgery - MUDASSAR ASLAM, YAHYA SAEED, IRAM ALIA (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the effectiveness of IV dexamethasone for the prevention of sore throat and hoarseness after tracheal intubation. We compare the effect of dexamethasone with placebo to reduce the incidence of postoperative sore throat. Method: Fifty ASA I – II patients undergoing elective orthopaedic surgery aged 20-50 years having tracheal intubation. Those patients having sore throat, Malampatti grade 3&4, Lane Cormack grade 3&4, more than one attempt at intubation and the duration of surgery longer than 4 hours were excluded. Patients were divided into two groups, Group A received I/V dexamethasoen 8mg and Group B received I/V saline one hour before surgery. The patients were evaluated at 0, 6, and 24 hours after surgery. The severity of sore throat assessed on 4 point scale. Results: The data was analyzed in SPSS version 15 and t test was used to compare the results. The incidence of sore throat was less in Group A as compared to Group B (P < 0.001). The incidence of hoarseness was also lower in group A than Group B (P < 0.05). Conclusion: The prophylactic used of 8mg dexamethasone IV significantly reduces the incidence and severity of sore throat and horarseness after orotracheal intonation.